1997
DOI: 10.1017/s0031182096008761
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the entire COWP gene of Cryptosporidium parvum and ultrastructural localization of the protein during sexual parasite development

Abstract: Molecular cloning and immunoelectron microscopy have been used to clone the full-length gene encoding Cryptosporidium parvum oocyst wall protein (COWP) and to analyse at the ultrastructural level the expression and localization of COWP during development in the gut. COWP is 1622 amino acids long, has a typical leader peptide and consists of 2 amino acidic domains each containing distinct repeated elements possibly originating from a common ancestral precursor. Electron microscopy localized COWP in a large cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 20 publications
4
91
0
Order By: Relevance
“…For COWP, the study by Jakobi and Petry (2006) showed that COWP expression was detected and peaked at 50 h and declined thereafter. Similarly, the study by Abrahamsen and Schroeder (1999) also reported that COWP mRNA levels in HCT-8 cell cultures were nearly undetectable from 6 to 24 h and dramatically increased at 48 h although in that study, COWP expression remained elevated at 72 h. In the current study, COWP expression in cell culture was also detected at 50 h and peaked at 50 h and 74 h (which is consistent with expression of the COWP gene exclusively by macrogametes (Spano et al, 1997) . In cell-free culture however, COWP expression was very low (0-52 gene copies) and peaked at 122 h. This suggests that the development of new oocysts in cell-free culture may be delayed compared to cell culture.…”
Section: Article In Presssupporting
confidence: 87%
See 1 more Smart Citation
“…For COWP, the study by Jakobi and Petry (2006) showed that COWP expression was detected and peaked at 50 h and declined thereafter. Similarly, the study by Abrahamsen and Schroeder (1999) also reported that COWP mRNA levels in HCT-8 cell cultures were nearly undetectable from 6 to 24 h and dramatically increased at 48 h although in that study, COWP expression remained elevated at 72 h. In the current study, COWP expression in cell culture was also detected at 50 h and peaked at 50 h and 74 h (which is consistent with expression of the COWP gene exclusively by macrogametes (Spano et al, 1997) . In cell-free culture however, COWP expression was very low (0-52 gene copies) and peaked at 122 h. This suggests that the development of new oocysts in cell-free culture may be delayed compared to cell culture.…”
Section: Article In Presssupporting
confidence: 87%
“…The gp900 gene is a microneme protein involved in invasion that has been detected in both sporozoites and merozoites (Bonnin et al, 2001;Cevallos et al, 2000;Petersen et al, 1992). The COWP gene has been localised in the wall-forming bodies of early and late macrogametes and the inner layer of the oocyst wall (Spano et al, 1997). Amplification of 18S rRNA was used as an indicator of total transcriptional activity.…”
Section: Article In Pressmentioning
confidence: 99%
“…For the C. parvum 5942 isolate oocysts were purified from Cryptosporidium-positive feces collected by the Cryptosporidium Reference Unit at the Singleton Hospital as part of the National Collection of Cryptosporidium Oocysts. Fecal isolates were confirmed by microscopic inspection of modified Ziehl-Neelsen-stained smears (3) and PCR-restriction fragment length polymorphism analysis of the Cryptosporidium oocyst wall protein gene (38). Briefly, oocysts were separated by flotation from fecal debris by using a saturated sodium chloride solution and centrifugation for 8 min at 1,600 ϫ g (36).…”
Section: Methodsmentioning
confidence: 99%
“…Each domain typically contains 6 cysteines, likely paired in disulfide bridges, which is reminiscent of other cysteine-rich apicomplexan domains such as the COWP protein family of the oocyst wall in coccidians [26,27]; the 6-Cys family that includes the Plasmodium gamete proteins Pfs230, Pfs47 and Pfs48/45 [28][29][30][31]; and the Toxoplasma SAG proteins [28,30,31]. The cpw-wpc gene family is widely conserved among apicomplexans, including Table 3).…”
Section: Cpw-wpc Proteins Are Composed Of Arrays Of a Domain Conservementioning
confidence: 99%